ESTETIKA FINISHING DAN PENERAPAN MATERIAL DALAM HUNIAN TETAP PASCA BENCANA DUSUN BATUR CANGRINGAN - Bambang Pramono (LINTAS RUANG: Jurnal Pengetahuan dan Perancangan Desain Interior, 2017)
As a topdown design policy, most of post-disaster permanent house requiring adaptation behavior of it occupans. The limitaion on space and budgets on setting lead to adaptation strategy choices.Since this reseach intense to observe the variation of finishing and materials applied, situated in of Batur Setlemen, a qualitative quantitave reseach mixed method with inductive analysis were applied. Variation of materials applied and finishing technique were found as result, folllowing by adaptation by adjustement as choosen strategy. Finantial background and future maintenance yield as result as the key factor of this fasad finishing tendencies.